Using Blockchain for Business & Marketing Improvement - Gatomatis, Panagiotis; Tsiomos, Konstantinos; Bogonikolos, Nikos (Journal of Marketing Development and Competitiveness, 2021)
In the 21st century's global business environment, there is a growing demand for credibility. Recent research has shed light on the global decline in trusting brands. Typically, trusted third parties have intervened to ensure the trust required for different business transactions. This paper examines the impact of Blockchain technology on business and marketing from a variety of perspectives. Conclusions are drawn regarding the anticipated course of business and marketing advances as a consequence of these technological advancements, culminating in the widely held belief that Blockchain innovations have the potential to fundamentally transform the economy, culture, political structures, and research activities in positive ways.